Monte Carlo simulations of krypton adsorption in nanopores: Influence of pore wall heterogeneity on the adsorption mechanism: Spectroscopy in Cryocrystals and Matrices - Kuchta, Bogdan; Llewellyn, Philip; Denoyel, Renaud; Firlej, Lucyna (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
We present molecular simulation results of the adsorption of krypton in a model of MCM-41 mesoporous material. The adsorption isotherm and adsorption enthalpies have been studied at 77 K. The comparison of experimental and simulation data allows us to analyze how the available interaction models (Kr–Kr and Kr–walls) are able to reproduce the experimental situation. The role of the heterogeneous interactions versus homogenous model is studied and compared with the previous simulation results of nitrogen adsorption in MCM-41. The results show that a model of ideal cylindrical pores gives qualitatively and quantitatively different results. A distribution of the adsorption sites must exist to explain the loading at low pressure (below capillary condensation). Such distribution in MCM-41 is a consequence of non-homogenous walls that contain a wide variety of attractive sites ranging from weakly attractive silica-type to highly attractive regions. In our simulations, the MCM-41 structure is modeled as an amorphous array of oxygen and silicon atoms, each one interacting with an adsorptive atom via the atom-atom potential. The distribution of the adsorption sites is merely a consequence of local atomic structure. Such a model of the wall reproduces the smooth increase in loading seen experimentally.